Host dispersal shapes the population structure of a tick-borne bacterial pathogen - Ana Cláudia Norte; Gabriele Margos; Noémie S. Becker; Jaime Albino Ramos; Maria Sofia Núncio; Volker Fingerle; Pedro Miguel Araújo; Peter Adamík; Haralambos Alivizatos; Emilio Barba; Rafael Barrientos; Laure Cauchard; et al. (WILEY, 2022)
Birds are hosts for several zoonotic pathogens. Because of their high mobility, especially of longdistance migrants, birds can disperse these pathogens, affecting their distribution and phylogeography. We focused on Borrelia burgdorferi sensu lato, which includes the causative agents of Lyme borreliosis, as an example for tick-borne pathogens, to address the role of birds as propagation hosts of zoonotic agents at a large geographical scale. We collected ticks from passerine birds in 11 European countries. B. burgdorferi s.l. prevalence in Ixodes spp. was 37% and increased with latitude. The fieldfare Turdus pilaris and the blackbird T. merula carried ticks with the highest Borrelia prevalence (92 and 58%, respectively), whereas robin Erithacus rubecula ticks were the least infected (3.8%). Borrelia garinii was the most prevalent genospecies (61%), followed by B. valaisiana (24%), B. afzelii (9%), B. turdi (5%) and B. lusitaniae (0.5%). A novel Borrelia genospecies "Candidatus Borrelia aligera" was also detected. Multilocus sequence typing (MLST) analysis of B. garinii isolates together with the global collection of B. garinii genotypes obtained from the Borrelia MLST public database revealed that: (a) there was little overlap among genotypes from different continents, (b) there was no geographical structuring within Europe, and (c) there was no evident association pattern detectable among B. garinii genotypes from ticks feeding on birds, questing ticks or human isolates. These findings strengthen the hypothesis that the population structure and evolutionary biology of tick-borne pathogens are shaped by their host associations and the movement patterns of these hosts.